KARAKTERISTIK MORFOLOGI DAN ANATOMI DAUN MANGGIS (Garcinia mangostana L.) DI KECAMATAN PAMONA UTARA - Ikbal, Muhammad; Adelina, Enny; Jeki, Jeki (AGROTEKBIS, 2018)
Mangosteen (Garcinia mangostana L.) has high economic value especially for export and it is potential to be developed into superior export commodities. Central Sulawesi has a promising potential for mangosteen development, but there are some disadvantages that must be corrected in advance such as the aspects of cultivation, production, harvest and post-harvest. The supply of qualified planting materials sourced from prospective parent tree is the first step that needs to be taken to improve mangosteen cultivation in Central Sulawesi mainly in Poso Regency. The research was carried out in Petirodongi and Sawidago villages of North Pamona district, Poso Regency. Leaves anatomical analysis was carried out at the Laboratory of Plant Pests and Diseases of the Faculty of Agriculture of Tadulako University. The research was conducted from December 2016 to February 2017. The research used explorative method, the data obtained employed cluster analysis. The analysis result of cluster results in Petirodongi Village reveal that there are various accession namely PD6 and PD14 in Sawidago district has four various accession such as SD4, SD9, SD10 and SD14. Meanwhile, the combination of the two villages obtained two accessions namely PD6 and SD4.